Identification of strategies for collaboration of medical librarians with family physicians in advancing the goals of the family physician program based on experts’ viewpoints - Ashrafi-rizi, Hasan; Amraei, Mahdi; Kargar, Hossein; Ghazavi, Zahra; Kazempour, Zahra (Journal of Contemporary Medical Sciences, 2019)
Objectives: The present study was carried out with the aim of identifying ways of collaboration of medical librarians with family physicians in advancing the goals of the family physician program based on the views of experts. Methods: This research was qualitative content analysis. The statistical population included experts in the fields of family physicians. Sampling method was targeted and in order to identify qualified people, snowball sampling was used as well. The data collection tool was semi-structured interview, and the researchers exploited thematic analysis in the data analysis. To determine the validity and reliability, the Lincoln and Guba method was used based on four criteria of credibility, transferability, conformability and dependability. Results: Regarding the common areas of medical librarians and family physicians, four concepts were extracted including helping physicians in scientific and professional mastering, upgrading research methodology, upgrading information literacy, and the content of information resources for patient training. Moreover, 4 concepts were identified: appropriate policy-making, education suitability, participation in clinical research, and promotion of the quality of patient training in addition to 6 components of interaction strategies. Conclusion: Strategies for the interaction of medical librarians with family physicians can become practical in areas such as proper policy-making, suitability of education, participation in clinical research, and the improvement of the quality of patient training.